Loss of PTEN Immunoexpression in Endometrial Carcinoma: A Narrative Review - Garima Chandrakar; Arvind Bhake (Journal of Clinical and Diagnostic Research, 2025)
Endometrial carcinoma is one of the important health issues addressed globally. Therefore, understanding the molecular pathogenesis of endometrial carcinoma for the purpose of prognostic and predictive markers remains in the centre of research. It has been reported in recently published literature that loss of Phosphatase and Tensin Homolog (PTEN) expression, a tumour suppressor gene, is one of the key events in the pathogenesis of endometrial carcinoma. This review aims to study the data for loss of PTEN expression in literature. Based on the inclusion and exclusion criteria, eight studies were finally included in the review. Comparative statistics of various studies showed that loss of PTEN expression is a key molecular event in endometrial carcinoma. The detection of lost PTEN expression could help in knowing the progressive nature of Atypical Endometrial Hyperplasia (AEH) and in distinguishing AEH from endometrial carcinoma. This will facilitate the choice of targeted therapy.